2021
DOI: 10.3390/ijms22137088
|View full text |Cite
|
Sign up to set email alerts
|

Fear Extinction and Predictive Trait-Like Inter-Individual Differences in Rats Lacking the Serotonin Transporter

Abstract: Anxiety disorders are associated with a failure to sufficiently extinguish fear memories. The serotonergic system (5-hydroxytryptamine, 5-HT) with the 5-HT transporter (5-HTT, SERT) is strongly implicated in the regulation of anxiety and fear. In the present study, we examined the effects of SERT deficiency on fear extinction in a differential fear conditioning paradigm in male and female rats. Fear-related behavior displayed during acquisition, extinction, and recovery, was measured through quantification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 103 publications
(181 reference statements)
4
8
1
Order By: Relevance
“…However, alarm calls during fear conditioning were not related to freezing at the end of extinction learning or across extinction retrieval, suggesting this behavior may not predict the success of extinction. Our findings are somewhat in contrast to Willadsen and colleagues (Willadsen et al, 2021b) who report positive correlations of the same behavior (alarm call rate, immobility time) within and across trial types, but weak or nonexisting crosscorrelation of alarm call rate with immobility. The lack of association was found for both withintrial and across-trial (fear acquisition correlated with extinction training) analyses.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, alarm calls during fear conditioning were not related to freezing at the end of extinction learning or across extinction retrieval, suggesting this behavior may not predict the success of extinction. Our findings are somewhat in contrast to Willadsen and colleagues (Willadsen et al, 2021b) who report positive correlations of the same behavior (alarm call rate, immobility time) within and across trial types, but weak or nonexisting crosscorrelation of alarm call rate with immobility. The lack of association was found for both withintrial and across-trial (fear acquisition correlated with extinction training) analyses.…”
Section: Discussioncontrasting
confidence: 99%
“…As the rat stock used for these experiments is outbred, the contribution of genetic variability to our findings is plausible. In an illustration of this possibility, knockout of the serotonin transporter gene reduces alarm call rates in male and female Wistar-crossed rats during fear conditioning ( Willadsen et al, 2021a ), and females from this strain emitted no alarm calls during extinction ( Willadsen et al, 2021b ). Previous work has also identified strain and sex differences in active and passive coping behaviors in repeated forced swim stress exposure ( Colom-Lapetina et al, 2017 ), so a stock or strain effect on vocalization patterns would not be unexpected and has indeed been demonstrated (Schwarting, 2018a , b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported impairments in FE recall for female rats when compared to male rats [65,66]. However, several studies have reported that females have greater FE rates when compared to males [67][68][69][70]. A recent review suggested that sex hormones may play an important role in conditioned FE, as estrous cycle influences may affect female FE mechanisms [71].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, female rats show a different behavioral response to fearful stimuli compared to the freezing of male, i.e. darting (Gruene et al, 2015; Han et al, 2020) but also in their USV emissions (Willadsen et al, 2021). This darting behavior is constituted by brief and high velocity movements in the experimental chamber.…”
Section: Discussionmentioning
confidence: 99%